2021
DOI: 10.1155/2021/8020879
|View full text |Cite
|
Sign up to set email alerts
|

Novel lncRNA Panel as for Prognosis in Esophageal Squamous Cell Carcinoma Based on ceRNA Network Mechanism

Abstract: Background. The competitive endogenous RNA (ceRNA) mechanism has been discovered recently and regulating cancer-related gene expressions. The ceRNA network participates in multiple processes, such as cell proliferation and metastasis, and potentially drives the progression of cancer. In this study, we focus on the ceRNA networks of esophageal squamous cell carcinoma and discovered a novel biomarker panel for cancer prognosis. Methods. RNA expression data of esophageal carcinoma from the TCGA database were achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In vitro experiments indicated that LOC105377626 functions as an oncogene in HCC cell lines, where it localized to the nucleus. The role of AC012073.1 in esophageal squamous cell carcinoma has been reported in only one risk score model study ( 57 ), where AC012037.1 was found to bind to miR-93. It also has prognostic value and participates in the competitive endogenous RNA network in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments indicated that LOC105377626 functions as an oncogene in HCC cell lines, where it localized to the nucleus. The role of AC012073.1 in esophageal squamous cell carcinoma has been reported in only one risk score model study ( 57 ), where AC012037.1 was found to bind to miR-93. It also has prognostic value and participates in the competitive endogenous RNA network in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above reports, this lncRNA is associated with cancer initiation and spread, can predict cancer prognosis reasonably and may become a potential molecular target. The results show that AC012073.1 has a critical prognostic value in esophageal squamous cell carcinoma ( Zhang et al, 2021 ). LINC00402 and other lncRNAs enhance PHLPP2 expression by competing with the endogenous RNA network and exerting repression in colon cancer pathogenesis ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…( 47 ) and Zhang et al. ( 48 ) successfully developed a novel three-lncRNA and six-lncRNA panel with prognostic value for EC patients by employing multiple Cox regression analysis, respectively. Similarly, Wang et al.…”
Section: Prognostic Signatures Based On Lncrna/circrna-mediated Cerna...mentioning
confidence: 99%
“…). For example, based on integrated analysis of lncRNA-mediated ceRNA network, Li et al(47) and Zhang et al(48) successfully developed a novel three-lncRNA and six-lncRNA panel with prognostic value for EC patients by employing multiple Cox regression analysis, respectively. Similarly, Wang et al(49) established a novel eight-gene signature as an independent prognostic factor for predicting the OS of patients with esophageal adenocarcinoma (EAC).…”
mentioning
confidence: 99%